The genus Campoplex Gravenhorst, 1829 (Hymenoptera, Ichneumonidae, Campopleginae) from China - Han, Yuan-Yuan; van Achterberg, Kees; Chen, Xue-Xin (Zootaxa, 2021)
The genus Campoplex Gravenhorst, 1829 (Hymenoptera, Ichneumonidae, Campopleginae) from China is revised. Thirty-nine new species are proposed (C. absitus sp. nov., C. acarus sp. nov., C. adustantennalis sp. nov., C. angustaulacis sp. nov., C. apacicarinatus sp. nov., C. artivultus sp. nov., C. atricrus sp. nov., C. collucatus sp. nov., C. concretus sp. nov., C. confluentus sp. nov., C. cyclus sp. nov., C. densipunctatus sp. nov., C. exareola sp. nov., C. granalvus sp. nov., C. grandialphus sp. nov., C. grandicella sp. nov., C. granulosus sp. nov., C. galbipedis sp. nov., C. hei sp. nov., C. liuae sp. nov., C. lobatus sp. nov., C. longiclypeus sp. nov., C. maurotrochanter sp. nov., C. medicarinatus sp. nov., C. monochroma sp. nov., C. obtusoclypeus sp. nov., C. parassosae sp. nov., C. perpendicularis sp. nov., C. proportionis sp. nov., C. protenus sp. nov., C. plicopunctatus sp. nov., C. pseudocyclus sp. nov., C. pseudostrigatus sp. nov., C. shanxiensis sp. nov., C. strigatus sp. nov., C. taenius sp. nov., C. tanae sp. nov., C. xizangensis sp. nov., and C. xuthomelonus sp. nov.) and one species is recorded as new to Nepal (C. oriens Gupta & Maheshwary). A key to Chinese species of Campoplex is provided.